(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article summarizes modern psychological approaches to increasing employee engagement and maintaining long-term high productivity. Key theoretical models (conditions of engagement, the Job model) are considered. Demands - Resources theory, self-determination theory), practical methods (job design, job crafting, psychological safety, goal-setting, feedback, and recovery), as well as principles for implementing and evaluating the effectiveness of interventions. Conclusions are drawn that a combination of organizational (resources, design) and individual-psychological (autonomy, meaning, and recovery) measures ensures the greatest sustainability of results.